Some aspects of spectral and microlocal methods in Mathematical General Relativity - Häfner, Dietrich (Comptes Rendus. Mécanique)
We review some of the important ideas of spectral and microlocal analysis which have been applied to problems in Mathematical General Relativity over the last decades.